2016
DOI: 10.1097/qai.0000000000000817
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Virologic Outcomes After Changes in First Antiretroviral Regimen at 7 Sites in the Caribbean, Central and South America Network

Abstract: Background HIV-infected persons in lower income countries may experience high rates of antiretroviral therapy (ART) change, particularly due to toxicity or other non-failure reasons. Few reports address patient outcomes after these modifications. Methods HIV-infected adults from 7 Caribbean, Central and South America network (CCASAnet) clinical cohorts who modified > or = 1 drug from first ART regimen (ART-1) for any reason thereby starting a second regimen (ART-2) were included. Results 5,565 ART-naïve HA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
2
7
0
Order By: Relevance
“…Better health seeking behaviour of women and earlier detection through Prevention of Mother To Child Transmission (PMTCT) interventions may contribute to the observed better outcomes. Low baseline CD4 + counts, use of AZT-based regimens and shorter duration on ART were associated with worse virologic outcomes in this study, consistent with ndings of other researchers in Africa and elsewhere [40][41][42][43][44][45][46][47].…”
Section: Discussionsupporting
confidence: 91%
“…Better health seeking behaviour of women and earlier detection through Prevention of Mother To Child Transmission (PMTCT) interventions may contribute to the observed better outcomes. Low baseline CD4 + counts, use of AZT-based regimens and shorter duration on ART were associated with worse virologic outcomes in this study, consistent with ndings of other researchers in Africa and elsewhere [40][41][42][43][44][45][46][47].…”
Section: Discussionsupporting
confidence: 91%
“…Although we did not report the reasons for changes in this population, a previous CCASAnet study with a larger number of ART-naïve patients initiating therapy over a wider time span found that the primary reason for early change was toxicity (57%), whereas treatment failure accounted for early change in only 5% of patients [ 22 ]. Recent CCASAnet data has shown that 61% of those who changed their first regimen changed to a third by 5 years [ 23 ]. Similar findings have been reported elsewhere, even in populations initiating HAART in more recent years [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antiretroviral therapy (ART) has changed the evolution of HIV infection, decreasing morbidity and mortality; however, it has some drawbacks [ 1 ]. Virological failure occurs in a significant proportion of patients [ 2 ] and represents one of the most challenging health management issues [ 3 ].…”
Section: Introductionmentioning
confidence: 99%